Chinese family businesses in Malaysia : fostering tacit knowledge innovation - Yew, Lee Kean (Routledge, 2025)
"Lee focuses on the historical and cultural journey of Chinese family businesses (CFBs) in Malaysia, uncovering the dynamic interplay of ethnic resources, generational knowledge, and state-led development policies that have shaped their survival and success. With one of the largest Chinese communities in Southeast Asia, Malaysia offers a rich landscape to explore the evolution of CFBs. Through analysing twelve small and medium-sized enterprises (SMEs) across key economic sectors, the book examines how Chinese family businesses have adapted to a shifting landscape, from leveraging deep-rooted networks and ethnic heritage to navigating government policies that have both challenged and shaped their growth. It uncovers key factors such as tacit knowledge, innovation, and generational transitions that have driven the evolution of these enterprises in Malaysia's competitive business environment. Drawing on detailed case studies, Lee demonstrates how tradition, innovation, and strategic decision-making converge to sustain business longevity across generations. An essential read for researchers, students, family business practitioners and business historians, and anyone interested in understanding the resilience and adaptability of Chinese family businesses"--